A study to look into the potential of Pistia Stratiotesin removing heavy metals from simulated waste water - Piakong Mohd Tuah (Universiti Malaysia Sabah, 2010)
Contamination of heavy metals in the environment is a major concern as It cannot be degraded chemically or biologically. Phytoremediation technology Is an easy and economic solution to remediate hea~ metals pollution. Study was carried out to determine the inoculation effect of Pb + tolerant strain on the removal of Pb2+ from simulated wastewater by floating aquatic macrophyte Pistia stratiotes which was chosen as It Is abundant locally with a net-like roots structure. The removal of heavy metals Pb2+, Cd2+, Ni2+ and Zn2+ was done in Continuous Vertical Inlet Flow (CVIF) reactor which provided adequate aeration to support roots system and enabled continuous removal process through filtration In the duration of 15 days. This macrophyte can survive in multiple heavy metals mixtures of ecr+, Pb2+, Ni2+ and Zn2+ at 1.5 mg\-1 ($ each meta\ fur S days without nutrients, 8 days In I-fold nutrients addition and 12 days In 2-fold nutrients addition. However, only Pb1 + was found to be removed 100 % from simulated wastewater and absorbed by P. stratlotes compared to ccf+, N12+ and Zn2+. Therefore, further analysis on heavy meta) removal by P. stratiotes was continued by focusing on Pb2+ alone which the plant was abte to survive up to 2.5 mgr1 • In microbiological study, eight strains were isolated from acid mine ora"mage and m'tzosp'nerit sarrqjJes 't."ch.en CIt 'C.'A-t'tam'Ut C~ ~, R~ 'IW. <liKed and enrichment technique on nutrient and Ramsay agar. Six strains were Gram positive rods, one was Gram negative rod and one was Gram positive cocci. These strains were tolerant towards Pb2 ... up to 100 mgr1 in Pb2+-modified broth. Strain NMeHI<r2 was found to be the most resistant strain at 100 mgr1 with the population of 8.94 x lOS CFU mrl. Pb2+ removal cap:cities (RC) of these strains however showed a different result where the htghest Pb + RC was shown by strain NMeHI-Crl (12.48 mgg-1 ) followed by NMeHI-Cr1 and NMeS2-W1 with 10.15 and 8.80 mgg-1 respectively. Strain NMeHI-Cr2 was identified as Bacillus cereus through molecular analysis. Inoculation of 8. cereus onto the roots of P. stratiotes had Increased the phytoremediation effldendes of the plants. This was shown by the complete removal of Pb2+from the simulated wastewater.